Early Season Wheat Response to Electrochemically Precipitated Struvite in Various Soils in the Greenhouse - Tatum Simms; Kristofor R. Brye; Trenton L. Roberts; Lauren F. Greenlee (Journal of Soil Science and Plant Nutrition, 2024)
Fertilizer-phosphorus (P) materials can be recovered from wastewater and used to supplement mined phosphate rock, where one such material is struvite [MgNH 4 PO 4 ·6(H 2 O)]. This study aimed to compare electrochemically precipitated struvite (ECST) reclaimed from synthetic wastewater to other commercial fertilizer-P sources in cultivated soils from Arkansas [silty clay loam (AR-SiCL) and silt loam (AR-SiL)], Missouri [(silt loam; MO-SiL 1 and 2)], and Nebraska [silt loam (NE-SiL) and sandy loam (NE-SL)]. A greenhouse pot study was conducted for 60 days with unvernalized wheat ( Triticum aestivum ) using five fertilizer-P sources [ECST, chemically precipitated struvite (CPST), monoammonium phosphate (MAP), triple superphosphate (TSP), and an unamended control (UC)] to evaluate treatment effects on below (BG)- and aboveground (ABG) and total dry matter (DM) and tissue-N, -P, -K, -Ca, -Mg, and -Fe uptakes. The ECST treatment produced 44 g m −2 larger ABG-DM than CPST in the AR-SiCL, but 181 g m −2 larger than the UC in the MO-SiL 1. The ECST had similar or larger nutrient uptakes than CPST, MAP, TSP, and UC. Belowground-P, -N, and -Mg uptakes for ECST were generally similar for all soil-fertilizer-P source combinations, where ECST was 0.3 to 2.6 g m −2 larger than all other fertilizer-P sources. Plant property response from ECST was generally similar to or greater than CPST, MAP, TSP, and the UC across all soils. Results suggest that ECST is a prime candidate to be used as an effective, alternative fertilizer-P source, suitable for use in wheat production across multiple soil textures.